2015
DOI: 10.7189/jogh.05.020401
|View full text |Cite
|
Sign up to set email alerts
|

Remoteness and maternal and child health service utilization in rural Liberia: A population–based survey

Abstract: BackgroundThis study seeks to understand distance from health facilities as a barrier to maternal and child health service uptake within a rural Liberian population. Better understanding the relationship between distance from health facilities and rural health care utilization is important for post–Ebola health systems reconstruction and for general rural health system planning in sub–Saharan Africa.MethodsCluster–sample survey data collected in 2012 in a very rural southeastern Liberian population were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 39 publications
3
38
2
Order By: Relevance
“…It is in line with Kenny et al (2015) that the long distance between dwelling place of a family and healthcare facilities may reduce the seek for and utilization of healthcare facilities moreover if accessing healthcare facility is costly. 6.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…It is in line with Kenny et al (2015) that the long distance between dwelling place of a family and healthcare facilities may reduce the seek for and utilization of healthcare facilities moreover if accessing healthcare facility is costly. 6.…”
Section: Resultsmentioning
confidence: 74%
“…The long distance between dwelling place of a family and healthcare facilities may reduce the seeking for and utilization of healthcare facilities (Kenny et al, 2015).…”
Section: Known As Complete Basic Immunization (Idl)mentioning
confidence: 99%
“…In the remaining 15 studies which did not use self-reported exposures, distance was measured or estimated using geographic data, including one (De Groot et al 1991 [ 26 ]) that interviewed women attending a HF for childbirth about their distance from home village, whilst address and other data for women with non-facility births were calculated using local census data. Among the other 14 studies, Nwakoby 1992 [ 28 ] measured distance directly on a printed map; and Kenny et al 2015 [ 29 ] tracked distance with a handheld positioning device during field workers’ travels to the communities for household interviews. The rest integrated geolocated data of women’s home or communities and a complete listing of HFs of the study area in a GIS.…”
Section: Resultsmentioning
confidence: 99%
“…At the first stage, we sampled villages with probability proportionate to size within each stratum using the standard DHS approach: listing clusters with a running cumulative number of households, determining the sampling interval necessary to take the correct number of clusters, randomly determining a starting value, and then selecting each subsequent cluster that corresponded to the sampling interval [ 42 – 44 ]. At the second stage, 21 households were selected per cluster in compact segments by (1) spinning a laminated paper triangle on the ground in the village’s center, (2) using a random number generator to randomly select an initial house in the direction pointed between the center and margin of the village, and (3) continuing to the next closest dwelling until 21 households were sampled [ 45 , 46 ]. We surveyed all women aged 18 to 49 in each selected household.…”
Section: Methodsmentioning
confidence: 99%